Limnological parameters in Skarvsnes lakes between the 47th and 48th Japanese Antarctic Research Expedition in 2006-2007 -Long-term monitoring study- - Kudoh, Sakae; Kasamatsu, Nobue; Hoshino, Tamotsu; Han, Dong-Hoon; Tanabe, Yukiko; Kanda, Hiroshi (National Institute of Polar Research, 2009)
P(論文) departmental bulletin paper